Writing for Clarity: A Concise Guide for Scientific Writing and Tips for Selecting a Journal - Thittayil Suresh Apoorv (Indian Journal of Radiology and Imaging)
Scientific writing is very important for writing research articles or commentaries. This article provides practical tips for researchers and clinicians to write well. Empowered researchers would be able to disseminate their research findings, help change the clinical practice, and advance public health.